Gender-Based Susceptibility to Mental Health Issues in Adolescents During the COVID-19 Pandemic: Descriptive Study - Young-Shin Lee; Minjeong Kim; Kim Moreno (Asian/Pacific Island Nursing Journal)
Abstract BackgroundAdolescence, the transitional phase between childhood and adulthood, is a stressful, fragile, and critical period. While the COVID-19 pandemic introduced numerous stressors affecting the mental health of all age groups, adolescents are particularly vulnerable. However, there is limited research focusing on the impact of COVID-19 on this population. ObjectiveThis study aimed to explore the impact of COVID-19, coping strategies, depression, anxiety, and post-traumatic stress disorder (PTSD) in adolescents during the pandemic. MethodsThis web-based cross-sectional survey study included 217 adolescents in Southern California, USA, between 2020 and 2021. Self-report measures include demographic questionnaires, COVID-19 impact, types of coping strategies used during COVID-19, depression, anxiety, and PTSD analyses. The χ2 ResultsFemale gender was identified as a risk factor for depression, anxiety, and PTSD. Approximately 24.2% (52/217) of participants had a family member or someone close who was infected with COVID-19 during the pandemic, which was a significant factor for both anxiety and PTSD (PP ConclusionsConsidering our findings, prevention programs focusing on mental health, including routine screening, should be implemented at community level for adolescents. School programs fostering healthy social interactions and education on coping strategies should also be implemented for both families and adolescents.